Bacterial translocation in abdominal trauma and postoperative infections (2011)
Background: Bacterial translocation (BT) describes the passage of bacteria residing into the gastrointestinal tract, through the intestinal mucosa barrier to sterile tissues such as mesenteric lymph nodes (MLN) and other organs. This phenomenon has not been thoroughly studied in patients with trauma to date, and an association between BT and postoperative infection has not been well established so far. Methods: MLNs from 36 patients with abdominal trauma were removed during laparotomy and cultured to detect BT. Postoperative infectious complications in these patients were registered, and both phenotypical and molecular typings (through multilocus sequencing) were carried out for microorganisms isolated from MLN and postoperative infection sites. Associations between clinical variables, BT presence, and postoperative infection development were established. Results: BT was detected in 33% of the patients (n = 12). Postoperative infections were present in 22.2% of the patients (n = 8). A significant statistical difference was found between postoperative infections in patients with BT evidence (41.6%), when compared with patients without BT (12.5%; p = 0.047). Bacteria isolated from infection sites were the same as those cultured in MLN in 40% of the cases (n = 2 of 5), allowing us to establish causality between BT and postoperative infection. Conclusions: There is higher risk of BT in trauma patients, and it is associated with a significant increase of postoperative infections. An abdominal trauma index ?10 was found to be associated with the development of BT. This is the first study describing BT among patients with abdominal trauma, where causality is confirmed at molecular level. Copyright © 2011 by Lippincott Williams and Wilkins.